Insights Into Genetic Variations of the OCT1 Gene in Metformin Poor Responders Among Bangladeshi Type 2 Diabetic Patients - Rokeya Begum; Arindita Das; Md. Jahangir Alam; Gazi Nurun Nahar Sultana (Advances in Pharmacological and Pharmaceutical Sciences)
Metformin is the most widely prescribed drug for the treatment of Type 2 diabetes mellitus (T2DM), but its response varies from person to person. This study aims to analyze the complete mutation spectrum of the OCT1 gene in metformin poor responders and to explore the potential pathogenic effects of the identified mutations. Clinical features of 56 Bangladeshi T2DM patients (who showed altered response to metformin) were analyzed, and genomic DNA was extracted from their blood samples. Subsequently, the entire exons (1–11), along with flanking introns of the OCT1 gene were amplified and sequenced. Molecular consequences of the identified mutations on OCT1 protein activity were determined through in silico analyses. In this study, 29 mutations of the OCT1 gene were identified; among which 5 mutations (c.412-86G>T, c.970G>C, c.1386-3088_1386-3083delGAATCA, c.1498+66G>T, and c.1653C>A) were novel. It was found that nsSNPs c.181C>T, c.1022C>T, c.493G>T, c.1207A>G, and c.970G>C (novel) as well as frameshift deletions have potential deleterious effects on OCT1 protein stability and function. Some of these mutations also cause alternative splicing, as per the HSF tool. In addition, alteration of interatomic bonding in the OCT1 protein due to two high-risk mutations (c.181C>T and c.1022C>T) was found from web-based analysis. The mutations, as mentioned earlier, are the most probable causative factor of decreased metformin effectiveness and adverse side effects in T2DM patients who are poor responders. Understanding the OCT1 gene variations of patients can help tailor treatment strategies for optimal metformin response or identify alternative medications.